Implementasi Insentif Pajak Penghasilan ditanggung Pemerintah Bagi UMKM di Masa Pandemi Covid-19 di Mataram Barat - Maelan Sari; Maria R.U.D. Tambunan (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
Tax incentives are waivers given by the government to taxpayers to develop the economic activities. Since pandemic Covid-19 occurred in Indonesia, it has brough the economic downturn, especially for the micro, small and medium enterprises (MSME) sector. To retain the MSME economic decline, the government has provided funding and incentives in the form of income tax final bear by government (or ditanggung pemerintah/DTP). However, the utilization of this incentives was less optimal even though the government has extended into several terms. The aims of this research are to assess the implementation of income tax incentive for MSME in West Mataram, considering West Mataram is highly supported by MSME for its economic activities and to assess factors affected the less optimal on application of that policy. This research used descriptive qualitative methods. Data collection was conducted through in-depth interviews and literature studies. The results showed that the tax officers have tried to apply the program, however it faced technical challenges which lead to suboptimal target. Factors affected the suboptimal target are such as lack of appropriate socialization by the tax officer, limited knowledge of MSME on taxation matters, and the unease of administrative processes which make the difficulties for MSME.